STRENGTHENING OF TRANSFORMATIONAL LEADERSHIP, EMPOWERMENT, WORK MOTIVATION AND TRUST IN ENHANCING TEACHER PROFESSIONAL COMMITMENT - Dedi Suryadi; Sri Setyaningsih; Martinus Tukiran (Journal of Industrial Engineering & Management Research, 2023)
This research was conducted using the correlation statistical method to determine whether other variables, namely transformational leadership, empowerment, work motivation, and trust have a positive relationship with teachers' commitment to the profession. Based on these results, an analysis was carried out using the Sitorem Method to make recommendations and determine which indicators should be repaired, maintained or developed immediately. Order of priority improvements that need to be made. The study was conducted at Bekasi City Public High School teachers, with a study population of 536 teachers and the sample of 145 teachers. The results showed that there was a positive relationship between transformational leadership, empowerment, work motivation, and trust on teacher’s professional commitment with the strength of the relationship ry1 = 0.476 and there was a positive relationship between work motivation and teacher professional commitment. The strength of the relationship ry2 = 0.264 is the strength of the relationship between transformational leadership and the commitment of the teaching profession, ry3 = 0.242 in trust towards the commitment of the teaching profession, and ry4 = 0.042, namely empowerment of the commitment of the teaching profession. This shows that the commitment of the teaching profession can be increased through transformational leadership, empowerment, work motivation, and trust. The results of the Sitorem Analysis show that there are 14 sequences of indicators that must be repaired immediately and 16 indicators that can still be maintained or developed.